Pengaruh Supervisi Klinis dan Kualifikasi Pendidikan Terhadap Kinerja Guru SDN Kecamatan Pakuhaji - Muhamad Sayuti Lukman (STKIP Andi Matappa Pangkep, 2022)
The quality of graduates and achievement of State Elementary School students in Pakuhaji District is low. This can be seen from the results of school examinations and student competition achievements at the district level in the last five years, the low performance of teachers due to lack of supervision and teacher education qualifications which are part of the cause. The research sample was 60 of 470 teachers which was carried out purposefully. The independent variables in this study were clinical supervision (X1) and educational qualifications (X2), while the dependent variable was teacher performance (Y). The measurements were carried out using a Likert scale while the data analysis used a two-way ANOVA. After the instrument was tested for validity and reliability, primary data was collected. The results of data processing showed that clinical supervision had a positive impact on teacher performance, compared to conventional supervision. Meanwhile, the educational qualifications of teachers who have a linear education in the field they are taught have better performance compared to teachers whose educational qualifications are not linear. The results of this study are that the linear treatment of clinical supervision and teacher education qualifications greatly affects their performance, therefore, it is better if the principal/education supervisor or educational institution that has the potential to determine policies in the provision of education should be able to increase clinical supervision activities and recruitment of educators in accordance with with educational qualifications.